2018
DOI: 10.1186/s12913-017-2817-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prolonged length of stay for elective hepatobiliary and neurosurgery patients: a retrospective medical record review

Abstract: BackgroundPatients with prolonged length of hospital stay (LOS) not only increase their risks of nosocomial infections but also deny other patients access to inpatient care. Hepatobiliary (HPB) malignancies have some of highest incidences in East and Southeast Asia and the management of patients undergoing HPB surgeries have yet to be standardized. With improved neurosurgery techniques for intracranial aneurysms and tumors, neurosurgeries (NS) can be expected to increase. Elective surgeries account for far mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 51 publications
0
33
0
3
Order By: Relevance
“…Our study identified several independent baseline associations with prolonged hospitalization. Other studies have similarly revealed that increasing age [ 12 , 17 , 18 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 33 , 34 , 36 , 38 , 39 , 40 , 50 ], female gender [ 22 , 24 , 26 , 30 , 36 , 39 , 50 ], not being in a relationship, [ 52 ] being a current smoker [ 39 ], level of co-morbidity [ 11 , 12 , 14 , 15 , 16 , 18 , 22 , 26 , 40 , 42 , 44 ], weekend admissions [ 42 ], and the number of prior admissions [ 25 , 32 , 44 ] were associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our study identified several independent baseline associations with prolonged hospitalization. Other studies have similarly revealed that increasing age [ 12 , 17 , 18 , 20 , 22 , 24 , 25 , 28 , 29 , 30 , 33 , 34 , 36 , 38 , 39 , 40 , 50 ], female gender [ 22 , 24 , 26 , 30 , 36 , 39 , 50 ], not being in a relationship, [ 52 ] being a current smoker [ 39 ], level of co-morbidity [ 11 , 12 , 14 , 15 , 16 , 18 , 22 , 26 , 40 , 42 , 44 ], weekend admissions [ 42 ], and the number of prior admissions [ 25 , 32 , 44 ] were associated with prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 94%
“…Most previous studies of prolonged hospitalization have focused on specific sub-groups of patients such as orthopaedic procedures [ 21 , 24 , 26 , 29 , 30 , 31 , 39 ], cardiovascular disease [ 13 , 15 , 17 , 36 , 37 , 38 ], solid organ transplantation [ 33 , 50 ], or oncological conditions [ 11 , 14 , 18 , 20 , 27 , 28 , 34 , 35 ] ( Supplementary Table S7 ). A limited number of studies have examined the epidemiology of prolonged hospitalization in internal medicine patients [ 23 , 45 , 51 ] but only one of these was multi-centre in nature [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,11 Longer LOS in itself can be considered a risk factor for postoperative morbidity, as it has been associated with other complications including thromboembolic events, infection, mood and mental status changes, higher risk for readmission, as well as consumption of hospital resources. 23 Thus, LOS can be used as an indirect marker for postoperative outcome and minimizing factors associated with longer LOS may be beneficial to both patients and caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Забезпеченість нейрохірургічними ліжками в 2019 р. становила 81 на 1 млн населення. Це високий рівень забезпеченості порівняно зі Швецією, Нідерландами, Норвегією та Великою Британією (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), але нижче, ніж у РФ (90), Чехії, Німеччині та Греції (100). Забезпеченість нейрохірургами на 1 млн населення і відношення кількості нейрохірургів до загальної чисельності населення в 2019 р. становило 16,8 та 1:59 502, що відповідає показнику в РФ (16,8 і 1:59 524), значно нижче, ніж в Японії (58,95 і 1:16 962, та вище, ніж у США (15,2 і 1:65 580).…”
unclassified